2002
DOI: 10.4049/jimmunol.169.3.1340
|View full text |Cite
|
Sign up to set email alerts
|

The Vα14 NKT Cell TCR Exhibits High-Affinity Binding to a Glycolipid/CD1d Complex

Abstract: Most CD1d-dependent NKT cells in mice have a canonical Vα14Jα18 TCR rearrangement. However, relatively little is known concerning the molecular basis for their reactivity to glycolipid Ags presented by CD1d. Using glycolipid Ags, soluble forms of a Vα14 NKT cell-derived TCR, and mutant and wild-type CD1d molecules, we probed the TCR/CD1d interaction by surface plasmon resonance, tetramer equilibrium staining, and tetramer staining decay experiments. By these methods, several CD1d α-helical amino acids could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 59 publications
(91 reference statements)
9
91
1
1
Order By: Relevance
“…Even though only *50% of a-GalCer-specific invariant NKT cells were detected by using a-GlcUCer, this proportion is significantly higher than that reported using PIM [6], and could indicate a subpopulation of NKT cells [31]. Unlike a-GalCer-loaded tetramers [30,32,33], the lipid-loaded CD1d-Ig dimers exhibit a Vbdependent staining of invariant NKT cells [31]. Therefore, the subset of NKT cells detected by a-GlcUCerloaded dimers have TCR with a-or b-chains that are not affected by the negatively charged carboxylic acid group Highlights 1697 of a-GlcUCer that distinguishes it from a-GalCer.…”
Section: A-glcucer Is the Nkt Cell Activating Ligandmentioning
confidence: 72%
“…Even though only *50% of a-GalCer-specific invariant NKT cells were detected by using a-GlcUCer, this proportion is significantly higher than that reported using PIM [6], and could indicate a subpopulation of NKT cells [31]. Unlike a-GalCer-loaded tetramers [30,32,33], the lipid-loaded CD1d-Ig dimers exhibit a Vbdependent staining of invariant NKT cells [31]. Therefore, the subset of NKT cells detected by a-GlcUCerloaded dimers have TCR with a-or b-chains that are not affected by the negatively charged carboxylic acid group Highlights 1697 of a-GlcUCer that distinguishes it from a-GalCer.…”
Section: A-glcucer Is the Nkt Cell Activating Ligandmentioning
confidence: 72%
“…Moreover, the reason for the apparent discrepancy of Con A and anti-CD3 mAb vs ␣-GalCer on NKT cell apoptosis is unknown. It is possible that the ability of Con A and anti-CD3 mAb to both directly activate the TCR (48) to mediate their effects, whereas ␣-GalCer is known to bind to CD1d before activation of the TCR (32,36,39) may underlie this discrepancy. Regardless, our data emphasize the fact that NKT cells are more prone to AICD when directly activated through the TCR.…”
Section: Discussionmentioning
confidence: 94%
“…NKT cells have the unusual property of recognizing glycolipid Ags in conjunction with the MHC class I-like molecule, CD1d (32)(33)(34)(35), and are abundant in the liver, thymus, and to a lesser extent in the spleen and bone marrow (31, 36 -39). Previous studies have demonstrated that CD1d gene-deficient and V␣14 gene-deficient mice, which express very few NKT cells, are resistant to Con A-induced hepatitis (11,24,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the natural antigen(s) that stimulate the majority of V␣14i NKT cells have not been unequivocally identified, V␣14i NKT cells are strongly reactive to a synthetic version of a marine sponge-derived glycolipid: ␣-galactosyl ceramide (␣-GalCer) (14). We and others have shown previously that the TCR of V␣14i NKT cells exhibits a high-affinity binding to the ␣-GalCer͞CD1d complex and a long half-life (t 1/2 ) (15)(16)(17)(18). ␣-GalCer is a very potent antigen, however, and it was not certain if those properties are linked to the peculiar nature of this antigen, or if they reflect the intrinsic requirements for the activation of V␣14i NKT cells.…”
Section: Ost T Lymphocytes Recognize Antigenic Peptides Presentedmentioning
confidence: 99%